المشكلات الأسرية في المجتمع الأندلسي القرنين: (04 – 09 هــ / 10 - 15م)بين - شريـــف عبد الناصر; نويكس عبد السلام; أ .د .خلفات مفتاح (كلية العلوم الإنسانية والاجتماعية, 2025)
الملخص بالعربية خلصت هذه الدراسة القائمة على بعض المصادر الفقهية الاندلسية، باعتبارها تحتوي على مادة علمية تاريخية تمكننا بعد فحصها وتحليلها من تشكل مصدرا أساسيا للعديد من أحوال الاسرة الاندلسية وللعديد من القضايا الاجتماعية والجوانب الحياتية الأخرى،فكان التوثيق لعقد الزواج والشروط التي تشترطها الزوجة للحفاظ على صيرورة الاسرة من تمليك لنفسها من خلال الطلاق او الخلع في حلات الضرر وغيرها. فالطلاق اعوص مشكلة في المجتمع الاندلسي وسع دائرة المشكلات والخلافات بين الاصهار والانساب وفي المجتمع عامة حيث طرحت عدَة قضايا منها الميراث وما نتج عنه، والنفقة والحضانة وتعدد الزوجات وخروج الزوجة من بيتها والزنا وغيرها فهي من المظاهر المشكلات الاندلسية وكيف أصبحت أسبابا لهذه المشكلات التي واجهت الاسرة الاندلسية. فعمل الفقهاء والقضاة على إيجاد حلول وعلاجات لهذه المشكلات الاسرية في المجتمع الاندلسي، وتم توثيقها وتسجيلها حفاظا على الحقوق. والبحث في هذا المجال لا يزال واسعا نظرا لما تزخر به كتب النوازل من وثائق وسجلات من ثروة علمية تفيد البحث التاريخي للمجتمع الاندلسي. الكلمات المفتاحية: المشكلات، الاندلسية، النزاعات، النوازل، المخطوطات، المصادر، مظاهر، أسباب، حلول، علاجات، الخلافات. This study, based on some Andalusian jurisprudential sources, concludes that they constitute a historical-scientific material which, upon examination and analysis, has formed a fundamental source for many aspects of Andalusian family life, social issues, and other life aspects. The documentation of marriage contracts and the conditions imposed by wives to safeguard family stability through divorce or annulment in cases of harm were highlighted. Divorce emerged as a significant problem in Andalusian society, widening the circle of disputes among relatives and communities in general. Various issues were addressed, including inheritance and its consequences, maintenance, custody, polygamy, wife's departure from home, adultery, among others, all representing challenges in Andalusian society and becoming the reasons for these problems faced by Andalusian families. Jurists and judges worked on finding solutions and treatments for these family issues in Andalusian society, documenting and recording them to preserve rights. Research in this field remains extensive due to the wealth of scientific documents and records in the books of "nawazil," which benefit historical research on Andalusian society. Keywords: problems, Andalusian, conflicts, nawazil, manuscripts, sources, aspects, reasons, solutions, treatments, disputes.